Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/9053663
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Nomogram-Based Prognosis Tools for Patients with Extremity Osteosarcoma: A SEER Population Study

Abstract: Objective. Osteosarcoma, usually occurring in the extremities, is the most common malignant bone tumour. The purpose of this study is to develop and validate nomogram-based prognosis tools for survival (OS) and cancer special survival (CSS) of patients with osteosarcoma of the extremities via the application of survival analysis. Materials and Methods. A total of 1427 patients diagnosed with osteosarcoma of the extremities during 2004–2015 were selected from the National Cancer Institute’s (NCI) Surveillance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…Improved CSS was associated with female sex compared with male sex and surgery compared with no surgery. The influencing factors are consistent with previous studies [7,34,37,[39][40][41].…”
Section: Discussionsupporting
confidence: 92%
“…Improved CSS was associated with female sex compared with male sex and surgery compared with no surgery. The influencing factors are consistent with previous studies [7,34,37,[39][40][41].…”
Section: Discussionsupporting
confidence: 92%
“…In our series, increasing age was protective, reducing the likelihood of mortality by 4%. In contrast, Huang et al 20 noted an increased risk of mortality in patients over the age of 22 years. This finding should, however, be interpreted cautiously amid the small sample size and the small number of patients aged over 30 years.…”
Section: Discussionmentioning
confidence: 89%
“…We observed that a single peak median age of 19 years (IQR 14.0 to 27.0) is similar to that previously reported in HICs. 4 , 20 , 21 Cole et al 4 and Duong et al 21 interrogated the epidemiology of osteosarcoma and emphasized bimodal distribution with an increased incidence rate in the second decade of life. In our series, increasing age was protective, reducing the likelihood of mortality by 4%.…”
Section: Discussionmentioning
confidence: 99%
“…The employment of validated nomogram has become more popular in clinical practice due to the model’s precision and usability. 101 In the TARGET cohort study of osteosarcoma patients, two significant independent risk factors, namely metastasis status and PRS-score level, were identified and were used to construct validated nomograms for predicting 1-, 2-, 3-, 4-, and 5-year OS rates. Previous studies 3 , 4 implied that 15–20% of osteosarcoma patients have detectable metastasis at diagnosis, 85–90% of which occurs in the lungs.…”
Section: Discussionmentioning
confidence: 99%